Pengembangan Motorik Kasar Anak Usia Dini Melalui Permainan Gerakan Binatang - Nuridayu Nuridayu; Aminoh Kiya; Ida Windi Wahyuni (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
Early childhood is the successor of the family that must be fostered and educated with various aspects of development. The child's gross motor includes all the muscular activities of the hands, feet, and all members of the body that integrate with the process of maturity in its coordination. Various studies on the development of gross motor skills of children, but in this study aims to determine the child's gross motor development through animal movement games. The research was carried out in PAUD IT Bunayya Pekanbaru in group A with a total of 16 students. This type of qualitative research that researchers apply to this study is to describe the learning outcomes that have been carried out so far by evaluating them through the results of the pretest and posttest. The results revealed that the gross motor development of children through animal movement games in PAUD IT Bunayya Pekanbaru can run well as expected, as the results of the percentage of pretest results of 31.35% have increased in the posttest results of 77.8%. In conclusion, namely the gross motor development of children through animal movement games develop very well. Keywords: development; gross motor skills; early childhood; movement; animalReferencesA. Agusriani. (2015). Peningkatan Kemampuan Motorik Kasar Dan Kepercayaan Diri Melalui Bermain Gerak. Jurnal Pendidikan Usia Dini, 9(1), 33–50. Anggraini, D. D., & Ittari, A. (2016). Peningkatan Keterampilam Motorik Kasar Melalui Kegiatan Tari Binatang pada Anak Kelompok B TK PGRI I Langkap. Jurnal PG-PAUD Trunojoyo: Jurnal Pendidikan dan Pembelajaran Anak Usia Dini, 3(2), 128–137. Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36. Fatihah, N., & Difla Nadjih. (2017). Hubungan Pendidik Dan Terdidik Dalam Al-Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 7(2), 73–86. Hidayat, F. (2016). Pengasuhan Anak Usia Dini Dalam Perspektif Psikologi. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 1–4. Huliyah, M. (2016a). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Huliyah, M. (2016b). Pengembangan Daya Seni Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Imroatun, I. (2014). Permainan Tradisional Sebagai Pembelajaran Kecakapan Sosial Bagi Anak Usia Dini. Jurnal Sains Psikologi, 3(1), 1–11. Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional Bagi Siswa Raudlatul Athfal. Al Hikmah Proceedings on Islamic Early Childhood Education, 103–112. Imroatun, I. (2017). Pembelajaran Huruf Hijaiyah bagi Anak Usia Dini. Proceedings of The 2nd Annual Conference on Islamic Early Childhood Education, 2, 175–188. Juhji, J. (2016). Pembelajaran Sains Pada Anak Raudhatul Athfal. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 49–59. L.E. Kusumaningtyas. (2016). Bermain dalam Rangka Mengembangkan Motorik pada Anak Usia Dini. Jurnal Ilmiah Pendidikan PraSekolah dan Sekolah Awal, 1(1), 47–56. Marwa, N. (2017). Upaya Meningkatkan Kemampuan Motorik Kasar Anak melalui Permainan Kelinci Melompat Pada Kelompok A PAUD As-Syifa Cilegon. Universitas Pendidikan Indonesia. Maulida, N., Anra, H., & Pratiwi, H. S. (2018). Aplikasi Pembelajaran Interaktif Pengenalan Hewan pada Anak Usia Dini. Jurnal Sistem Dan Teknologi Informasi (JUSTIN), 6(1), 26–31. Mutiara, S. N. (2016). Meningkatkan Kemampuan Motorik Halus Anak Melalui Permainan Lego Block. Jurnal Pertumbuhan Perkembangan Anak Usia Dini, 13(2), 170–178. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. Nuridin. (2013). meningkatkan Keterampilan Motorik Kasar Anak Melalui Stimulasi Gerak Binatang. Universitas Pendidikan Indonesia. Nuryanti, Roni, R., & Ismail, H. (2015). PENGEMBANGAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI KEGIATAN SENAM CERIA. Cakrawala Dini: Jurna Pendidikan Anak Usia Dini, 6(2), 101–111. Nuryati, N. (2017). Pengembangan Kecerdasan Spiritual Pada Anak Usia Dini Melalui Murottal Bacaan Al-Quran. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 17–26. Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Rozia, I., & Khotimah, N. (2017). Peningkatan Kemampuan Motorik Kasar Anak Melalui Permainan Lompat Kelinci pada Anak Kelompok A di TK Islam Terpadu Ceria Mojoagung Jombang. PAUD Teratai, 6(3), 1–7. Setiani, & Nadjih, D. (2016). Pembentukan Karakter Anak Usia Dini Melalui Pendidikan Agama Islam Di TK ABA Kalibulus Rogobangsan Bimomartani Ngemplak Sleman. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 6(2`), 125–136. Sujiono, B., & dkk. (2014). Metode Pengembangan Fisik. Universitas Terbuka. Sunanto, S., & Hardiningrum, A. (2018). Pengembangan Dalam Motorik Kasar Melalui Permainan Melempar Dan Menangkap Bola Di Kelompok A PPT Matahari Gunungsari Surabaya. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 3(1), 73–79. Tejaningrum, D. (2017). Peningkatan Kemampuan Berbicara Melalui Metakognitif Pada Anak Dengan Gangguan Pemusatan Perhatian Dan Hiperaktivitas. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 37–46. https://doi.org/10.1017/CBO9781107415324.004Ubaedah, D., Fatimah, A., & Kusumawardani, R. (2019). Meningkatkan Keterampilan Motorik Kasar melalui Senam Irama Binatang. Jurnal Penelitian Dan Pengembangan Pendidikan Anak usia Dini, 6(1), 29–40. Uswatun Hasanah. (2016). Pengembangan Kemampuan Fisik Motorik melalui Permainan Tradisional bagi Anak Usia Dini. Jurnal Pendidikan Anak, 5(1). Veronica, N., Yuliati, L., & Akbar, S. (2017). PERKEMBANGAN KOGNITIF DAN TEORI BELAJAR SOCIO CULTURAL PADA ANAK USIA DINI. Prosiding Seminar Nasional Teknologi Pembelajaran dan Pendidikan Dasar 2017, 402–408. Wahyuni, I. W., & A. Muazimah. (2020). Pengembangan Motorik Kasar Anak melalui Permainan Tradisional" Tarik Upih" Berbasis Kearifan Lokal. Jurnal Pendidikan Anak Usia Dini Undiksha, 8(1), 61–68. Y.N Sujiono. (2013). Konsep Dasar Pendidikan Anak Usia Dini. PT. Indeks.